Hukum Islam terhadap Pemanfaatan Barang Gadai (Rahn): Analisis Komparatif Ulama dan Praktik Kontemporer - Muhammad Absah Fajar Asy’ari; Rina Siti Nurhayati; Nazwa Syakira Putri Darmawan (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article discusses the utilization of pawned goods (rahn) from the perspective of Islamic law. This discussion is motivated by the many pawning practices carried out by the community to meet economic needs, thereby raising legal issues regarding whether or not pawned goods can be utilized by the pledgee (murtahin). The purpose of this article is to understand the definition of pawning in Islamic fiqh, understand the legal basis of pawning, explain the provisions for the utilization of pawned goods according to scholars, and determine its implementation in modern life. The method used is a literature study by examining sources from the Al-Qur'an, hadith, fiqh books, and scientific literature related to the rahn contract. The results show that pawning is a permitted contract in Islam based on the Al-Qur'an, hadith, and scholar consensus (ijma). However, there are differences of opinion regarding the utilization of pawned goods. Some scholars strictly prohibit utilization to avoid elements of usury (riba), some allow it on the condition of permission from the owner (rahin) and not agreed upon in the contract, while others allow it as compensation for goods maintenance costs. In modern practice, Islamic pawnbroking institutions generally do not utilize pawned goods and only charge maintenance fees (ujrah) to maintain compliance with sharia principles. Thus, the utilization of pawned goods must consider the principles of justice, mutual assistance, and avoid usury practices to remain in accordance with the provisions of Islamic law.   Keywords: Fiqh Muamalah, Pawn (Rahn), Islamic Law, Sharia Pawnshops, Utilization of Pawned Goods